The Reconstruction of Aisyah’s Marriage Age as a Resolution For Child Marriage Practices Phenomenon - Adawiyah, Robi'atul; Mukhlisa, Dian; _, Yuliatin; Putra, Devrian Ali (Universitas Islam Negeri Raden Intan Lampung, 2022)
The Reconstruction of Aisyah’s Marriage Age as a Resolution For Child Marriage Practices Phenomenon. The marriage of Aisyah bint Abu Bakr at a young age with the Prophet Muhammad is often used to legitimize the permissibility of marrying small children in the Islamic world. This is what makes the practice of child marriage difficult to eradicate in Muslim-majority countries. This study aims to see how the impact of child marriage on children, the efforts of Muslim scientists in eradicating the practice of child marriage through the reconstruction of Aisyah's marriage age as well as the government's efforts to eliminate the practice of child marriage during the pandemic. This study is library research using a qualitative approach. The results show that Aisyah's marriage at the age of 6 years was not relevant to the existing evidence. Second, it is true that Aisyah bint Abu Bakr married the Prophet Muhammad at a very young age of 9 or 10 years, but that age was considered appropriate for marriage in the cultural context of people around the world at that time. Third, the government's action to increase the age of marriage to 19 years for men and women is something that is in line with the objectives of Islamic law (maqāshid al-sharī'ah). Based on these findings, the practices of early child marriage should be prevented, and even prohibited because it is against Islamic Law.